Influence of Experimental Learning Models on Cognitive Learning Outcomes in Energy Transformation Material in the Independent Curriculum - Fatimatuzzahro Fatimatuzzahro; Farid Ahmadi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to test the effect of experimental learning models on the cognitive learning outcomes of 4th grade elementary school students on the material of energy transformation in the Independent Curriculum. Quantitative methods with quasi-experimental designs were used, involving all 4th grade elementary school students in Tugu District, Semarang City, divided into experimental and control classes. The experimental class was taught using an experimental learning model, while the control class used the lecture method. Cognitive learning outcomes were measured using tests that included indicators of essential competency achievement in the material of energy transformation. Data were analyzed using normality tests, homogeneity tests, t tests, N-Gain tests, and hypothesis tests to compare the average post-test scores between the two groups. The results showed a significant difference between students' cognitive learning outcomes in the two groups. The data obtained in the t stat column or tcount was 4.005, and the Critical two-tail or ttable was 1.972. The tcount > ttable = 4.005 > 1.972 was obtained based on this. So, it can be concluded that, with a significance level of 5%, Ha is accepted and H0 is rejected. This study concludes that the experimental learning model positively affects students' cognitive learning outcomes on energy transformation material in the Independent Curriculum and can be an effective alternative to improve cognitive learning outcomes